Platforms and network effects - Paul Belleflamme; Martin Peitz (University of Mannheim, Department of Economics, 2016)
In many markets, user benefits depend on participation and usage decisions of other users giving rise to network effects. Intermediaries manage these network effects and thus act as platforms that bring users together. This paper reviews key findings from the literature on network effects and two-sided platforms. It lays out the basic models of monopoly platforms and platform competition, and elaborates on some routes taken by recent research.
urn:nbn:de:bsz:180-madoc-413065
Keywords: D43; L13; L86; 330; Network effects; digital platforms; two-sided markets; tipping; platform competition; intermediation; pricing; imperfect competition